Deltas in the Anthropocene - Nicholls, Robert J.; Adger, W. Neil; Hutton, Craig W.; Hanson, Susan E. (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
The Anthropocene is the human-dominated modern era that has accelerated social, environmental and climate change across the world in the last few decades. This open access book examines the challenges the Anthropocene presents to the sustainable management of deltas, both the many threats as well as the opportunities. In the world's deltas the Anthropocene is manifest in major land use change, the damming of rivers, the engineering of coasts and the growth of some of the world's largest megacities; deltas are home to one in twelve of all people in the world. The book explores bio-physical and social dynamics and makes clear adaptation choices and trade-offs that underpin policy and governance processes, including visionary delta management plans. It details new analysis to illustrate these challenges, based on three significant and contrasting deltas: the Ganges-Brahmaputra-Meghna, Mahanadi and Volta. This multi-disciplinary, policy-orientated volume is strongly aligned to the United Nation's Sustainable Development Goals as delta populations often experience extremes of poverty, gender and structural inequality, variable levels of health and well-being, while being vulnerable to extreme and systematic climate change. Robert J Nicholls is Professor of Coastal Engineering within Engineering and Physical Sciences at the University of Southampton, UK. He has contributed to a wide range of influential national and international publications including the IPCC Assessment Reports. W Neil Adger is Professor of Human Geography at the University of Exeter, UK. His research examines demographic, political economy, public health and well-being aspects of the Anthropocene. Craig W Hutton is Professor of Sustainability Science within Geography and Environment at the University of Southampton, UK. His research focuses on spatial analysis of vulnerability and the incorporation of sustainable management, policy and governance into decision-making processes. Susan E Hanson is Research Fellow within Engineering and Physical Sciences at the University of Southampton, UK. She specializes in coastal vulnerability and management, particularly as a consequence of climate change.